2013
DOI: 10.1590/s1517-86922013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos agudos e crônicos de um programa de alongamento estático e dinâmico no rendimento em jovens atletas do futebol

Abstract: Introduction: Stretching is a therapeutic technique and may be used as a form of warm-up to increase flexibility or decrease pain throughout the movement, with objective to improve performance and reduce the risk of injury. Objective: To verify the acute and chronic effects of a program of static stretching compared with the dynamic one in performance of young soccer athletes. Methods: Randomized clinical study of equivalence carried out between August and November, 2010 with the under-17 category of the Grêmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
2
0
4
Order By: Relevance
“…Assim como no presente estudo, os ganhos de ADM foram identificados por pesquisas que aplicaram a intervenção crônica da flexibilidade, seja pelo emprego do método estático (Ferreira, Salmela & Guimarães, 2007. Gonçalves, Pavão & Dohnert, 2013Mahieu et al, 2007;Minshull et al, 2014;Yildirim, Ozyurek, Tosun, Uzer & Gelecek, 2016), seja pela FNP (Gama et al, 2007;Kwak & Ryu, 2015;Konrad, Gad, & Tilp, 2015, Rees, Murphy, Watsford, Mac Lachlan & Coutts, 2007.…”
Section: Tabelaunclassified
“…Assim como no presente estudo, os ganhos de ADM foram identificados por pesquisas que aplicaram a intervenção crônica da flexibilidade, seja pelo emprego do método estático (Ferreira, Salmela & Guimarães, 2007. Gonçalves, Pavão & Dohnert, 2013Mahieu et al, 2007;Minshull et al, 2014;Yildirim, Ozyurek, Tosun, Uzer & Gelecek, 2016), seja pela FNP (Gama et al, 2007;Kwak & Ryu, 2015;Konrad, Gad, & Tilp, 2015, Rees, Murphy, Watsford, Mac Lachlan & Coutts, 2007.…”
Section: Tabelaunclassified
“…A combinação de exercícios de flexibilidade, realizados de forma estática ou dinâmica é amplamente utilizada nos dias atuais, pela evidência de que este tipo de método parece exercer resultados mais satisfatórios quando comparado aos métodos passivos treinamento (Coelho, 2007;Gonçalves, Pavão, & Dohnert, 2013). Todavia, estudos atuais vem apontando e que os usos destas metodologias podem refletir num menor rendimento do atleta que utiliza a potência como tipo de força predominante (Rubini et al, 2011;Škarabot et al, 2015).…”
Section: Protocolo De Exercício De Flexibilidadeunclassified
“…Num estudo recente, Gonçalves e seus colegas compararam dois grupos de atletas de futebol formados em função de dois métodos de flexibilidade num experimento de avaliação crônicos: dinâmica e passiva (Gonçalves et al, 2013). Neste estudo ficou evidente que o alongamento dinâmico, pode ser uma forma de promover ativação muscular no período pré-treino ou pré-jogo, mas que o método passivo demonstrou melhorar a impulsão vertical e os níveis de flexibilidade.…”
Section: Protocolo De Exercício De Flexibilidadeunclassified
“…Kokkonen et al (15) reported that the muscle strength of knee flexors and extensors, jump performance, and sprint time were improved after a 10-week SS intervention, which consisted of 15 types of SS for various lower-extremity muscles including the hamstrings. Regarding specifically hamstring stretching, some studies demonstrated no change in isokinetic or isometric strength after a chronic SS intervention (11,17,20); however, Worrell et al (32) reported that isokinetic strength increased after a 3-week SS intervention. The lack of consensus regarding the chronic effect of SS on muscle strength may be because the SS duration or intensity in these studies was insufficient to reduce musculotendinous unit stiffness, or because different types of contraction (i.e., isokinetic and isometric contraction) were used to assess muscle strength among studies.…”
Section: Introductionmentioning
confidence: 99%